Reality television and Arab politics : contention in public life - Kraidy, Marwan M., 1972- (Cambridge ; New York : Cambridge University Press, 2010)
What does it mean to be modern outside the West? Based on a wealth of primary data collected over five years, Reality Television and Arab Politics analyzes how reality television stirred an explosive mix of religion, politics, and sexuality, fueling heated polemics over cultural authenticity, gender relations, and political participation in the Arab world. The controversies, Kraidy argues, are best understood as a social laboratory in which actors experiment with various forms of modernity, continuing a long-standing Arab preoccupation with specifying terms of engagement with Western modernity. Women and youth take center stage in this process. Against the backdrop of dramatic upheaval in the Middle East, this book challenges the notion of a monolithic "Arab Street" and offers an original perspective on Arab media, shifting attention away from a narrow focus on al-Jazeera, toward a vibrant media sphere that compels broad popular engagement and contentious political performance.
Introduction: beyond al-Jazeera -- Screens of contention: the battle for Arab viewers -- Voting Islam off the island? Big brother in Bahrain -- The Saudi-Lebanese connection -- Contesting reality: Star academy and Islamic authenticity in Saudi Arabia -- Gendering reality: Kuwait in the eye of the storm -- A battle of nations: Superstar and the Lebanon-Syria media war -- The "new Middle East"? Reality television and the "independence Intifada" -- Conclusion: performing politics, taming modernity.
economic&political bookfair2015
Includes bibliographical references (p. 221-244 and index.
Keywords: Reality television programs -- Arab countries -- History and criticism; Reality television programs -- Political aspects -- Arab countries; Television viewers -- Arab countries -- Attitudes; Public opinion -- Arab countries